Low prevalence of resistance genes in sheltered homeless population in Marseille, France, 2014–2018 - Ly, Tran Duc Anh (Infect Drug Resist, 2019)
Objectives: The present study has explored the prevalence and potential factors contributing to the presence of nasal/pharyngeal resistant genes in homeless people. Methods: During the winters 2014–2018, we enrolled sheltered homeless adults and controls and collected nasal/pharyngeal samples. Sixteen antibiotic resistance genes (ARGs), including genes encoding for beta-lactamases and colistin-resistance genes, were searched by real-time polymerase chain reaction (qPCR) performed directly on respiratory samples and followed by conventional PCR and sequencing. Results: Over a 5-year period, using qPCR, we identified in homeless group (n=715) the presence of bla(TEM) (396/710, 54.7%), bla(SHV) (27/708, 3.6%), bla(OXA-23) (1/708, 0.1%), while other genes including colistin-resistance genes (mcr-1 to mcr-5) were absent. We found a significantly higher proportion of ARG carriage among controls (74.1%) compared to homeless population (57.1%), p=0.038. Tobacco smoking (OR=4.72, p<0.0001) and respiratory clinical signs (OR=4.03, p=0.002) were most prevalent in homeless people, while vaccination against influenza (OR=0.31, p=0.016) was lower compared to controls. Among homeless people, type of housing (shelter A versus B, OR=1.59, p=0.006) and smoking tobacco (smoker versus non-smoker, OR=0.55, p=0.001) were independent factors associated with ARG carriage. By sequencing, we obtained a high diversity of bla(TEM) and bla(SHV) in both populations. Conclusion: The lower risk for ARGs in the homeless population could be explained by limited access to health care and subsequently reduced exposure to antibiotics.